Notes about Joaquín Rodrigo - Hernandéz Madriz, Walter (2004)
The intention of these notes about Joaquín Rodrigo is to become familiar with the most successful composer in Spanish musical history, someone exceptional in the twentieth century in the world, not only for the extensiveness of his production but also for its excellent quality.